Geomechanical justification of rock mass stability during underground limestone mining in quarry walls - A.O. Ostapchuk; O.O. Frolov (Технічна інженерія)
The results of numerical simulation of the behavior of the quarry side during limestone excavation in the software package PLAXIS 3D are presented.